Immersive Science Communication: Using Virtual Reality to Bridge Civil Security Research and Policy-Making - Lindner, Ann-Kathrin; Terfurth, Leonie; Gerhold, Lars; Schiller, Jochen (Proceedings of the International ISCRAM Conference, 2026)
Science-policy communication faces numerous challenges, such as prioritizing issues by urgency and relevance, and incomplete policy preferences due to ambiguous approaches to solutions. Virtual reality (VR) offers new possibilities for addressing these challenges. Specifically, it has been shown to affect knowledge and attitudes. This paper details the design and implementation of a VR application developed to address the specific requirements of policy audiences in the context of civil security research. The application follows a modular design, showcasing demonstrator-level innovations from five civil security research projects. A central hub allows users to access project modules independently, tailoring the experience to political priorities and time constraints. By allowing users to experience the cause-and-effect relationships of innovations in realistic crisis scenarios, the application aims to support the practical adoption of solutions. The potential of the approach will be explored through systematic evaluation in future work.